2017
DOI: 10.1007/s00221-017-5023-3
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation of Peptide5 systemic administration for treating traumatic spinal cord injured rats

Abstract: Systemic administration of a Connexin43 mimetic peptide, Peptide5, has been shown to reduce secondary tissue damage and improve functional recovery after spinal cord injury (SCI). This study investigated safety measures and potential off-target effects of Peptide5 systemic administration. Rats were subjected to a mild contusion SCI using the New York University impactor. One cohort was injected intraperitoneally with a single dose of fluorescently labelled Peptide5 and euthanised at 2 or 4 h post-injury for pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 85 publications
0
13
0
Order By: Relevance
“…Other studies by Gourdie and colleagues used a peptide targeting the carboxyl tail of Cx43 and its binding site with the PDZ domain to improve wound healing, resolve inflammation and reduce scarring in rat models and recently in human clinical trials [ 33 , 34 , 35 ]. Studies using Pep5, based on the Gap27 sequence, have shown remarkable effects on tissue repair and inflammation in the retina, cornea and spinal cord [ 36 , 37 , 38 ]. Recent studies using Gap27 have also shown that this peptide is effective in improving rabbit corneal wound healing [ 39 ] and in primary human gingival fibroblasts, isolated from donors aged 26–48 years of age [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Other studies by Gourdie and colleagues used a peptide targeting the carboxyl tail of Cx43 and its binding site with the PDZ domain to improve wound healing, resolve inflammation and reduce scarring in rat models and recently in human clinical trials [ 33 , 34 , 35 ]. Studies using Pep5, based on the Gap27 sequence, have shown remarkable effects on tissue repair and inflammation in the retina, cornea and spinal cord [ 36 , 37 , 38 ]. Recent studies using Gap27 have also shown that this peptide is effective in improving rabbit corneal wound healing [ 39 ] and in primary human gingival fibroblasts, isolated from donors aged 26–48 years of age [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Though the interaction between Cx43 and molecules involved in pain offers a complicated feedback loop in pain development and maintenance, based on the current studies, strategies to suppress the function of Cx43 may be a robust approach for pain relief (Wu et al, 2011; Chen et al, 2012, 2014; Shen et al, 2014; Xu et al, 2014; Neumann et al, 2015; Robinson and Dougherty, 2015; Choi et al, 2016; Hang et al, 2016; Kaji et al, 2016; Mao et al, 2017a,b; Wang and Sun, 2017; Yang et al, 2018).…”
Section: Astrocytes and Cx43 In Chronic Painmentioning
confidence: 97%
“…The expression changes of Cx43 following pain is still inconclusive (Table 2). Multiple studies have shown that Cx43 is upregulated in astrocytes following nerve ligation and spinal cord injury, and that inhibition of Cx43 can attenuate pain hypersensitivity (Wu et al, 2011; Chen et al, 2012, 2014, 2018; Shen et al, 2014; Neumann et al, 2015; Robinson and Dougherty, 2015; Choi et al, 2016; Hang et al, 2016; Kaji et al, 2016; Mao et al, 2017a,b; Wang and Sun, 2017; Yang et al, 2018). On the contrary, few studies showed that a decrease of Cx43 following nerve injury could contribute to pain hypersensitivity (Xu et al, 2014; Morioka et al, 2015; Zhang et al, 2016).…”
Section: Astrocytes and Cx43 In Chronic Painmentioning
confidence: 99%
See 1 more Smart Citation
“…Since neuroinflammation has both beneficial and detrimental effects, broadspectrum suppression of inflammation may not be efficacious. Neuroprotection can also be achieved through preventing glutamate excitotoxicity by blockade of NMDA receptors by magnesium (Ditor et al, 2007) or gacyclidine (Feldblum et al, 2000), blockade of tetrodotoxin-sensitive sodium channels using riluzole (Satkunendrarajah et al, 2016), preventing apoptosis using erythropoietin (Baptiste & Fehlings, 2006), inhibition of connexin hemichannels using a mimetic peptide (Mao et al, 2017), mild to moderate hypothermia (Dietrich et al, 2009) and many more strategies (Baptiste & Fehlings, 2006;Thuret et al, 2006). These more discrete manipulations of secondary processes may prove to have greater therapeutic benefit than the broad approaches.…”
Section: Reticulospinal Tractmentioning
confidence: 99%